Die neuen Solo-Selbständigen zwischen Unternehmergeist und Prekarität - Candeias, Mario (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
The entrepreneur is the central figure in the neoliberal discourse. The trend towards selfemployment is therefore interpretated as a sign for entrepreneurial thinking becoming the basis for general interest articluation, far beyond particular class interest. But in fact the real situation of most of the self-employed clearly points to a social position as independent workers, entangled in contradictions between self-management and a new sense of freedom on the one and harsh dependencies and self-exploitation on the other side. The article tries to elaborate on specific differences and common elements between workers and self-employed. It becomes clear, that the independent workers are part of the rising precariat and could share common interests with other precarious workers. What is needed is to overcome the very individualistic habits of the self-employed. Far from beeing sufficient, new forms of collective organisation such as the Euromayday or an Italian union for precarious independent workers are pointing into this direction.